2017
DOI: 10.3346/jkms.2017.32.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable Course of Subclinical Hypothyroidism in Children with Hashimoto’s Thyroiditis Compared to Those with Isolated Non-Autoimmune Hyperthyrotropinemia

Abstract: Subclinical hypothyroidism (SCH) is a common problem in pediatric population, and the natural history of SCH varies depending on its etiology. Whether Hashimoto’s thyroiditis (HT) negatively affects the natural course of SCH was investigated in pediatric patients without concomitant diseases. Predictors for levothyroxine medication were also evaluated. Medical records of 109 children with SCH (91 girls, 5−18 years) diagnosed between 2005 and 2014 were retrospectively reviewed. Patients were classified into HT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
(40 reference statements)
0
11
1
Order By: Relevance
“…20,21 Subclinical hypothyroidism is frequently observed in T1DM. 13,[21][22][23][24][25][26][27] We found no significant association between duration of diabetes and TSH levels in children with T1DM. Past studies have shown that the longer the duration of diabetes, the higher the prevalence of autoimmune thyroiditis.…”
Section: Discussioncontrasting
confidence: 67%
“…20,21 Subclinical hypothyroidism is frequently observed in T1DM. 13,[21][22][23][24][25][26][27] We found no significant association between duration of diabetes and TSH levels in children with T1DM. Past studies have shown that the longer the duration of diabetes, the higher the prevalence of autoimmune thyroiditis.…”
Section: Discussioncontrasting
confidence: 67%
“…Subclinical hypothyroidism (SHT) (or isolated hyper-thyrotropinemia)—defined as a mild elevation of serum TSH concentration and a normal peripheral thyroid hormones concentration—has a prevalence of 1.7% in the pediatric population [ 43 ] and is more common in obese pediatric patients than in normal-weight patients (24.3% vs. 12.8%, p = 0.002) [ 44 ]. Thyroidal and non-thyroidal diseases may induce SHT, among which the most common are Hashimoto’s disease and isolated non-autoimmune hyper-thyrotropinemia, the latter being more prevalent in obese children [ 45 , 46 ]. In adults, NLR is more increased in patients with malignancy than in patients with benign thyroid nodules and is associated with a higher degree of thyroid function loss [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…6) HT is characterized by the existence of thyroid autoantibodies (antithyroid peroxidase [TPO Ab] and antithyroglobulin [TG Ab]) with or without goiter. 7) Patients with HT may develop subclinical or overt hypothyroidism depending on the intensity of the immunological injury. 8) 2.…”
Section: Hashimoto's Thyroiditismentioning
confidence: 99%